Prompt Engineering P2X Business Ecosystem with Generative AI - Tani, Toni; Yläkujala, Antti; Metso, Lasse; Sinkkonen, Tiina; Kärri, Timo (Procedia computer science, 2025)
This study examines the potential of generative Artificial Intelligence (AI) in visualizing and sketching Power-to-X (P2X) business ecosystems via the Business Ecosystem Prompt2X Method (BEP2X). Utilizing advancements in GPT technology, this approach offers a dynamic alternative to traditional static visualization methods. Guided by the research questions, this study investigates the role of generative AI in ecosystem categorization, led by prompt engineering for detailed visualization, and culminates in the creation of a tangible artifact through this process. Using the DSR framework, BEP2X is introduced as a new method for applying generative AI to draw complex business ecosystems. The synthetic methanol plant project in Finland serves as a case study in its development, illustrating BEP2X’s practical utility.